Decreased renal organic anion transporter 3 expression in type 1 diabetic rats - Arjinajarn Phatchawan (2018)
BACKGROUND: Organic anion transporter 3 (Oat3) plays an essential role in the renal excretion of organic anions. Reduced renal Oat3 expression potentially contributes to an impaired anion clearance and causes abnormal kidney function. This study examined the effects of diabetes on the expression and function of rat renal Oat3. METHODS: Experimental diabetes was induced by the administration of streptozotocin. Diabetic rats were randomly assigned to the treatment group or no treatment group with insulin for 4 weeks. The expression of renal Oat3, protein kinase Cα (PKCα), phospho-PKCα and nuclear factor kappa B (NF-κB) p65 were determined by immunoblotting. Estrone sulfate (ES) uptake into renal cortical slices was used as an indicator of renal Oat3 function. RESULTS: The reduced expression of renal Oat3 was related to the decrease in [H]ES uptake in a renal cortical slice of the diabetic rat. Insulin treatment restored the impairment of renal Oat3 function and expression. These may be because of the hyperglycemia-induced oxidative stress effectively activating the PKCα and NF-κB. Insulin treatment abolished these processes. CONCLUSIONS: These data are the first to show that the decreased function and expression of renal Oat3 in diabetes was associated with an increase in reactive oxygen species production coinciding with the activation of PKC and NF-κB signaling pathway. These events may affect the transporter protein translocation and/or expression.